Degradation of the surface of a metasilicate glass due to atmosphere moisture - Ziemath, E. C. (Soc Brasileira Quimica, 1998)
Glasses with low silica content are very susceptible to suffer pronounced degradation when exposed to room atmosphere during short times. In this work the results of the degradation of the surface of a metasilicate glass with composition 2Na(2)O.1CaO.3SiO(2) are presented. Optical and scanning electron microscopy observations, X-ray diffraction, infrared and Raman microprobe spectroscopic measurements of the modified surface of this glass show strong evidences that it is formed essentially by a crystalline carbonate layer.
Keywords: oxide glass; surface corrosion; vibrational spectroscopy